ANALISIS EFISIENSI ENERGI PADA PROSES PENGERINGAN GABAH MENGGUNAKAN DRYER GRAINPRO 30T-HS DI PT KARUNIA TRINITAS AGRO - I Wayan Joniarta; Yoga Raditya Ananda Putra; Made Wijana; I Kade Wiratama (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2025)
Rice is a key food commodity that plays a strategic role in maintaining national food security. One of the important stages in post-harvest processing is grain drying, as excessive moisture content can reduce rice quality and accelerate deterioration during storage. This study aims to analyze energy efficiency in the grain drying process using the GrainPro 30T-HS dryer at PT Karunia Trinitas Agro. The research method was conducted through direct observation with measurements of grain moisture content, drying temperature, process duration, husk fuel consumption, and electricity usage. The results showed that grain moisture decreased from 25.1% to 12.5% with a total mass of 23,000 kg. The drying process was carried out at 60 °C for 17 hours, with husk consumption of 1,500 kg and electrical power of 19 HP. Based on the calculation, the energy efficiency of the dryer reached 34.65%, which is relatively higher compared to other studies on biomass-fired batch dryers. This finding highlights that utilizing rice husks as fuel is not only economical but also environmentally friendly, thus the GrainPro 30T-HS can be recommended as an efficient drying system for industrial-scale applications..